Desimination of Technology for Utilizing Online Learning Media during the Covid-19 Pandemic at SD Muhammadiyah Mlangi - Nur Faidati; Enny Fitriahadi (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
The COVID-19 pandemic has had a significant impact on the life of the world community, including in Indonesia. In addition to health impacts, the pandemic also has economic, educational and social impacts. In the field of education, the Government through the Minister of Education and Culture of the Republic of Indonesia issued Circular Letter Number 4 of 2020 concerning the Implementation of Education Policies in the Emergency Period for the Spread of COVID 19. Responding to this, teachers in schools must be creative in preparing interesting learning methods according to learning needs. One of these interesting learning methods can be prepared by utilizing digital media. SD Muhammadiyah Mlangi is one of the educational institutions of Muhammadiyah Charity (AUM) which currently needs to increase the capacity of human resources to deal with the dynamics of the environment that is currently happening. The aspect of developing the capacity of human resources related to the ability in online learning will also increase the achievement of the material to be conveyed by educators. The PKM implementation method that will be carried out is divided into three major stages, namely preparation, socialization activities, training activities/workshops towards the target. In this training, teachers practice using a number of applications that have never been used before, such as quiziz, bitmoji and kahoot. These applications will still be useful for creative and innovative learning processes even though they are no longer in online learning. This is related to the target of education today is the digital native generation.